CORRELATION BETWEEN URINARY CASTS AND BIOCHEMICAL MARKERS OF RENAL FUNCTION IN CHILDREN WITH ACUTE GLOMERULONEPHRITIS - Dr. Nasir Islam; Dr. Muhammad Awais Niaz; Dr. Muhammad Salman Zafar; Dr. Asna Ijaz; Dr. Shahid Ishaq; Dr. Jamal Asad (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: Acute glomerulonephritis (AGN), particularly post-streptococcal glomerulonephritis (PSGN), remains a significant cause of pediatric renal morbidity in Pakistan, especially in rural and low-income urban communities where overcrowding, poor sanitation, and limited access to healthcare prevail. Urinary sediment analysis particularly the presence of red blood cell (RBC) casts is a key diagnostic indicator, while serum creatinine and blood urea serve as standard biochemical markers of renal dysfunction. However, the quantitative correlation between urinary cast types and the severity of renal impairment in Pakistani children has not been systematically evaluated. OBJECTIVE: To assess the correlation between urinary casts (RBC and granular) and biochemical markers of renal function (serum creatinine and blood urea) in children diagnosed with AGN at a tertiary care hospital in Lahore, Pakistan. MATERIALS AND METHODS: A prospective observational study was conducted at The Children Hospital and the Institute of Child Health, Multan, from January 2023 to December 2024. Sixty-five children aged 2–12 years with confirmed AGN were enrolled. Diagnosis was based on clinical features (hematuria, edema, hypertension) and evidence of recent streptococcal infection (elevated ASO titer, skin or throat infection). Urine microscopy for casts, serum creatinine, and blood urea were measured at admission. Statistical analyses included Pearson’s correlation, independent t-tests, and linear regression (p < 0.05 considered significant). RESULTS: RBC casts were present in 72.3% of patients, granular casts in 7.7%, and no casts in 20.0%. Elevated blood urea (>40 mg/dL) was observed in 32.3% of cases; serum creatinine >1.0 mg/dL in 10.8%. A strong positive correlation existed between RBC casts and blood urea (r = 0.64, p < 0.001) and serum creatinine (r = 0.59, p = 0.001). Mean blood urea was significantly higher in RBC cast-positive patients (49.2 ± 13.1 mg/dL vs. 31.8 ± 10.2 mg/dL; p < 0.001). Similarly, mean serum creatinine was elevated in this group (1.14 ± 0.33 mg/dL vs. 0.82 ± 0.20 mg/dL; p = 0.002). Granular casts correlated moderately with azotemia but were infrequent. CONCLUSION: The presence of RBC casts strongly correlates with impaired renal function in Pakistani children with AGN, underscoring their value as a bedside predictor of disease severity. Early identification of casts in urine sediment can guide timely intervention and monitoring in resource-limited settings.